Harmonizing electricity laws in South Asia. (Asian Development Bank, 2017)
South Asia, home to nearly one sixth of the global population, is one of the poorest regions in the world. Access to electricity in the region is low and the South Asian Association for Regional Cooperation (SAARC) member countries face acute electricity shortages, adversely impacting their socioeconomic development. Yet the region is endowed with hydropower potential, coal reserves, natural gas reserves, large renewable energy resources, and petroleum reserves. These can be harnessed to become key drivers of the regions growth and energy trade has the potential to capitalize on this asset.